Correlation between serum albumin and creatinine levels in children with nephrotic syndrome - Gartika Sapartini; Dedi Rachmadi; Herry Garna (Paediatrica Indonesiana, 2008)
Background Nephrotic syndrome is a glomerular disordercharacterized by massive proteinuria, hypoalbuminemia, edema,and hyperlipidemia. Hypoalbuminemia in nephrotic syndromeleads to hypovolemia, a decrease in renal perfusion and glomerularfiltration rate. Serum creatinine level reflects the glomerularfiltration rate.Objective The aim of this study was to determine the correlationbetween serum albumin and creatinine levels in children withnephrotic syndrome.Methods A cross-sectional study was carried out on children withidiopathic nephrotic syndrome, aged between 1 to 14 years old,admitted to Pediatric Department in Hasan Sadikin Hospitalfrom January 2001 to September 2007. We used data frompatients' medical records to obtain serum albumin and creatininelevels during nephrotic stage. Statistical analysis using Pearsoncorrelation test was performed to establish the correlation betweenserum albumin and creatinine levels. The type of correlation wasdetermined by regression analysis.Results Subjects were 113 children, consisted of 81 boys (72%)with mean of age 6.8 (SD 3.3) years. Mean of serum albumin andcreatinine levels were 1.4 (SD 0.4) g/dL and 0.7 (SD 0.4) mg/dL, respectively. Analysis using Pearson correlation test showeda moderate (r=-0.478) significant correlation (P<O.Ol) betweenserum albumin and creatinine levels in children with nephroticsyndrome. Regression analysis suggested a negative linearrelationship between serum albumin level as the independentvariable (X) and serum creatinine level as the dependent variable(Y) by using equation Y = 1.328-0.460X.Conclusion In patients with nephrotic syndrome there is amoderate negative correlation between serum albumin andcreatinine levels.